ANALISIS HUKUM PIDANA ISLAM DALAM PUTUSAN NOMOR:1632//PID.SUS.2018/PN.PLG TENTANG PEMBERIAN DATA TIDAK SAH - Oktaviani, Irma; Huzaimah, Arne; Safithri, Hijriyana (Universitas Islam Negeri Raden Fatah Palembang, 2020)
With regard to Decision Number: 1632 / Pid.Sus.2018 / PN.PLG Regarding Providing Illegal Data to Obtain Travel Documents According to Undang-Undang Nomor 6 Tahun 2011 Tentang Keimigrasian, it is necessary to study the basis for judges' considerations in deciding the case. In addition, the author also intends to analyze it from the point of view of Islamic criminal law. The method used in this research is a library research approach. The data source used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the research show that the criminal sanctions in the Criminal Act deliberately provide invalid data to obtain the Travel Documents of the Republic of Indonesia in Decision Number: 1632 / Pid.Sus / 2018 / PN.PLG is 8 (eight) months imprisonment and a fine of Rp. .5,000,000, - (five million rupiah) provided that if the fine is not paid, it is replaced by imprisonment for 3 (three) months. Meanwhile, according to Islamic Criminal Law, Ta'zir punishments are imposed in the form of volume punishment and exile punishment. Keywords: Data Falsification, Falsification of Immigration Documents, Ta'zir.